STUDY OF WOODEN PILE FOUNDATION STRUCTURE IN STAGE HOUSES ON THE BANYUWANGI COAST - Sunarko (Bulletin of Engineering Science, Technology and Industry, 2023)
This research aims to determine the structure of the foundation of wooden pillars in stilt houses on the coast of Banyuwangi. The method used in the discussion is descriptive analysis, namely analyzing study object data based on theory related to the topic and object of observation, with the aim of finding the system and form of construction applied to The foundations of residential houses in this village correspond to three zones, namely water, transition and land. The final results conclude the form of the structural system and foundation construction of residential houses in each regional zone. The foundations of the houses in each zone show that on land the houses use pile foundations, in transitions with stone masonry, and on the water using stone masonry and some directly with pillars.